Comparative analysis of the clinical efficacy of conservative treatment for adenomyosis using traditional Chinese medicine and Western medicine - Yan Liang; Tianling Xiao; Haiyan Zhang (Journal of Health, Population and Nutrition)
Abstract Objective To explore the clinical efficacy of commonly used conservative treatments for adenomyosis using both TCM and Western medicine. Methods 210 patients with adenomyosis were selected and divided into 3 groups: Group A (Dan’e Fukang), Group B (Dienogest), and Group C (Goserelin + Mirena), with 70 cases in each group. Afterward, indicators were collected for comparison. Results Different treatment approaches exhibited varying effects on uterine VAS, and PBAC among the 3 groups (P < 0.001). The effects of different treatment approaches on serum levels of estradiol (E2), FSH, and CA125 also differed among the 3 groups (P < 0.001). After 3 months of treatment, the incidence of adverse reactions among the 3 groups was significantly different (P < 0.001), with further comparison indicating a lower incidence of adverse reactions in Groups A and B than in Group C (P < 0.017). Meanwhile, statistically significant differences in the incidence of adverse reactions among the 3 groups were observed again after 6 months of treatment (P = 0.004), with further comparison revealing a lower incidence of adverse reactions in Group B than in Group C. Additionally, the comparison of uterine volume (P < 0.001) and VAS (P < 0.001) among the 3 groups was different after 12 months of treatment, and further comparison revealed that the uterine volume was ranked as Group B > Group C > Group A, while the pelvic pain VAS scores were ranked as Group C > Group B = Group A. Conclusion Dan’e Fukang Decoction is markedly effective in alleviating pain; Goserelin + Mirena exhibits significant efficacy in reducing bleeding.